Mycoplasma pneumoniae and Mycoplasma genitalium mixture in synovial fluid isolate. - Tully, J G (1995)
A mycoplasma cultured from synovial fluid specimens from a patient with pneumonia and subsequent polyarthritis was identified initially as Mycoplasma pneumoniae. In retrospective studies, the culture was shown also to contain Mycoplasma genitalium. In this paper, the laboratory techniques employed in the identification and separation of the two species are presented, and evidence to implicate postinfectious autoimmunity is provided. An increasing number of reports of M. genitalium in human tissue sites and difficulties in isolation and identification of the organism in the clinical laboratory suggest the need for more extensive application of rapid and specific detection systems for both M. genitalium and M. pneumoniae in the clinical laboratory.